Participatory Research: A Feminist Critique - Jackson, Carey Ann; Van Vlaenderen, Hilda (PINS-Psychology in Society, 2026)
South Africa is currently going through a process of transformation. In this process policy making is a major concern of those who are responsible to steer the country through the period of change into a satisfactory new socio-economic order. Although the principles of democracy, non racism and non sexism have been widely accepted as the foundation for the new South Africa, these concepts need to be operationalised into specific policies in the various fields of government. In order to do this, research is required at all levels of society, ranging from grassroots groups to national structures. The authors argue the inherently political nature of scientific research, meaning that scientific knowledge is an important tool in maintaining or shifting the balance of power. As Carasco (1983: 2) puts it: "Research, as a channel of inquiry and investigation with the potential to generate powerful knowledge and information, can be either liberating or repressive. It can lead to either decisive socio-political action on the part of an entire community or to the exclusion or manipulation of that community by an ’informed’ minority". It is further argued that the producer of what is considered scientific knowledge have predominantly been white, middle class, male and that they have used that knowledge to preserve the rights of their own group in society as well as to institutionalise a continued oppression of others, namely working class, black or female. The traditional, "male stream" research paradigm has maintained and reinforced the subordinate position of women in society. A Feminist Research paradigm will be presented as an alternative paradigm that contributes to the liberation of women and that allows for conducting non sexist, non racist research. Subsequently a Participatory Research paradigm will be introduced. The authors believe that Participatory Research provides a methodology appropriate for libratory grassroots research. Participatory Research will then be submitted to a Feminist Research critique with the aim of developing a gender sensitive Participatory Research approach.